2018
DOI: 10.15345/iojes.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reading Motivations of 6th, 7th and 8th Grade Students on Reading Attitudes: A Structural Equation Modeling

Abstract: In this study, it was aimed to analyze the reading motivations of 6th, 7th and 8th graders on reading attitudes through structural equation modeling, as well as their reading attitudes and motivations in terms of different variables. In the research carried out by the relational and descriptive scanning model, the study group formed by simple random sampling consisted of 349 6th, 7th and 8th grade students. The Survey of Adolescent Reading Attitudes (SARA) developed by Baştuğ and Keskin (2013) and the Motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Attitudes and motivation toward reading will lead students to a greater possibility for success (Akkaya & Kirmizi, 2010). The relationship between students' attitudes toward reading and their reading and comprehension achievement has been extensively researched in the literature (ARICAK., 2008;Azizi et al, 2020;Baki, 2018;Hashemi & Na, 2020;McKenna & Kear, 1990;Roomy & Alhawsawi, 2019;Rosales, 2020;Zaccoletti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes and motivation toward reading will lead students to a greater possibility for success (Akkaya & Kirmizi, 2010). The relationship between students' attitudes toward reading and their reading and comprehension achievement has been extensively researched in the literature (ARICAK., 2008;Azizi et al, 2020;Baki, 2018;Hashemi & Na, 2020;McKenna & Kear, 1990;Roomy & Alhawsawi, 2019;Rosales, 2020;Zaccoletti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researchers (Dong & Hu, 2019;Molla et al, 2020;Resilla, 2018) tried to elaborate about relationship between gender and reading ability. The findings shown that female students performed better in reading literacy than male students (Baki, 2018;Resilla, 2018). However, the finding differed from Molla et al, (2020) who founded that was no significant relationship between gender and student reading abilities.…”
Section: Student Factormentioning
confidence: 79%
“…This is because, external factors such as parental involvement at home (Dawkins, 2017), the influence of schools such as lack of infrastructure (Sukasni & Efendy, 2017) and the student factor itself (Chen et al, 2019) also presided over the reading ability factors. Past studies have tried to identify the association between reading and student motivation (Baki, 2018) teacher quality (Rosser, 2018), and gender as an indicator that influences reading abilities (Molla et al, 2020). There are also studies that try to associate students' reading abilities with family factors such as family socioeconomic levels (Nawas, 2019) the level of parents' education (Aditomo & Hasugian, 2018) and early literacy activities such as reading storybook to children before they go to bed (Wijayanti, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırma sonuçları okuma motivasyonunun yüksek olmasının okumaya yönelik olumlu tutum gelişimini de etkilediğini göstermektedir (Baki, 2018). Bu bakımdan okuma motivasyonunun belirlenmesi öğrencilerin bireysel farklılıklarının anlaşılması, evde veya okulda okuryazarlık deneyimlerine yardımcı olunabilmesi bakımından önemlidir (Baker ve Wigfield, 1999).…”
Section: Suggestionsunclassified